2017
DOI: 10.1021/acs.jced.7b00638
|View full text |Cite
|
Sign up to set email alerts
|

Solubility Measurement and Correlation of Fosfomycin Sodium in Six Organic Solvents and Different Binary Solvents at Temperatures between 283.15 and 323.15 K

Abstract: The solubility data of fosfomycin sodium (FOM-Na) in six pure solvents (methanol, ethanol, propanol, cyclohexane, acetone, N,N-dimethylformamide) and two binary solvents (methanol + ethanol, methanol + acetone) at temperatures ranging from 283.15 to 323.15 K were measured by a laser monitoring dynamic method at atmospheric pressure. It turned out that the solubility data decreased with increasing temperature, and also varies with the composition of the solvents. Moreover, the experimental data in pure solvents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 27 publications
(40 reference statements)
0
11
0
Order By: Relevance
“…where A 0 −A 8 are adjustable parameters and obtained by leastsquares analysis. 34,35 The values of the above model parameters were optimized by minimizing the following objective function with experimental solubility data:…”
Section: Resultsmentioning
confidence: 99%
“…where A 0 −A 8 are adjustable parameters and obtained by leastsquares analysis. 34,35 The values of the above model parameters were optimized by minimizing the following objective function with experimental solubility data:…”
Section: Resultsmentioning
confidence: 99%
“…The mole fraction solubility ( x A ) of calcium formate (form α) in different binary solvent mixtures was calculated by eq , and the initial mole fraction ( x B ) of the organic solvent (methanol, ethanol, n -propanol, and acetone) of the binary solvent mixtures can be calculated by eq as follows where m 1 , m 2 , and m 3 denote the masses of calcium formate, organic solvents (methanol, ethanol, n -propanol, and acetone), and water, respectively. M 1 , M 2 , and M 3 represent the molecular weights of calcium formate, organic solvents (methanol, ethanol, n -propanol, and acetone), and water, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…However, previous study already reported that the drug was weakly basic compound with pKa and log P of 7.49 and 2.46, respectively [ 1 ]. Hence, in this study, the solubility of the model drug in methanol, ethanol, 1-propanol, 2-propanol, 1-butanol, 2-butanol, acetonitrile, acetone, ethyl acetate, Transcutol ® HP (THP), water, and in Transcutol ® HP–water mixture (TWM) was determined at temperatures ranging from 298.15 K to 318.15 K under atmospheric pressure using the static equilibrium method [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. The modified Apelblat model (AM), van’t Hoff model (VHM), and Buchowski–Ksiazaczak λh model (BKM) were used to correlate the experimental solubility in selected organic solvents [ 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%